Pengaruh Stres Kerja Dan Beban Kerja Terhadap Kepuasan Kerja Karyawan PT. Thamrin Brother’s Lahat - Deky Fujiansyah (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
The purpose of this research is to determine the effect of job stress and workload to job satisfaction of employees of PT. Thamrin Brother's Lahat. The research sample included 30 employees of PT. Thamrin Brother's Lahat. Test instrument test in this study are validity and reliability test for questionaure. Test requirements analysis include: data normality test, the linearity of the data, multiple linear regression, t test, F test and determination coefficient. The result of this research give the regression model . Based on the results of SPSS, value of correlation (r) is 0.839, it can be concluded that the variable work stress and workload variables have a very strong relationship to employee job satisfaction variable PT. Thamrin Brother's Lahat. The value of coefficient of determination (R2) is 0,704. This means that the influence of employee job satisfaction variable PT. Thamrin Brother's Lahat can be explained by work stress and workload variable with contribution of 70,4%, while the rest of 29,6% can be explained by other variable not included in this research model. Partial t-test show result that job stress and woakload both has the positive significant influence to job satisfaction. Simultant test with F-test show that job stress and workload as a whole have a significant effect on employee work satisfaction PT. Thamrin Brother's Lahat.